2007
DOI: 10.1007/s00436-007-0622-8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of the Prevalence and Genotype Distribution of Giardia intestinalis in Dogs in Hungary

Abstract: In the genus Giardia (G.) intestinalis is the only species found in humans as well as in other mammals, including domestic and farm animals. Molecular characterisation of strains isolated from different hosts revealed the existence of seven major genotypic assemblages. Assemblage A and B isolates have been recovered from a broad range of hosts, including humans, livestock, cats, dogs, beavers and guinea pigs. Infection and subsequent cyst shedding contaminates the environment for all mammals, including humans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
4
12
1
1
Order By: Relevance
“…This favours easy maturation of larvae and oocysts as it is not the case in the temperate countries where less prevalences were reported. The overall prevalence intestinal parasites of (59.3%) is similar with the findings of Papini et al (2005) and Szenasi et al (2007) who discovered high prevalence of infection of 55.2% and 58.8% in dogs respectively elsewhere.…”
Section: Resultssupporting
confidence: 87%
“…This favours easy maturation of larvae and oocysts as it is not the case in the temperate countries where less prevalences were reported. The overall prevalence intestinal parasites of (59.3%) is similar with the findings of Papini et al (2005) and Szenasi et al (2007) who discovered high prevalence of infection of 55.2% and 58.8% in dogs respectively elsewhere.…”
Section: Resultssupporting
confidence: 87%
“…Decreasing age has previously been implicated as an important risk factor for canine giardiosis (Bugg et al, 1999;Capelli et al, 2006;Szénàsi et al, 2007) and is probably related to immunological naivety to the pathogen (Szénàsi et al, 2007). Development of immunological competence may also explain why dogs kennelled for more than 12 months had a lower prevalence of infection.…”
Section: Discussionmentioning
confidence: 98%
“…Although Papini et al (2005) and Szénàsi et al (2007) found high prevalences of infection of 55.2% and 58.8% in kennelled dogs using a G. duodenalis-specific coproantigen ELISA, the discrepancy found by Szénàsi et al (2007) between prevalence as determined by this method and by microscopy (7.5%) suggests some caution should be applied in use of this diagnostic method (Cirak and Bauer, 2004;Mekaru et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various methods used, higher infection rates were detected by PCR or enzyme-linked immunosorbent assay (ELISA) than by conventional microcopy. For example, in two studies, the infection rates were 3.3% and 7.5% when micros- copy was used, whereas the rates were 12.9% and 58.8% when ELISA was used (194,251). In another study, the infection rates were 3.0% by microscopy and 20.0% by PCR (265).…”
Section: Public Health Importance Of Giardiasismentioning
confidence: 99%